2019
DOI: 10.1109/access.2019.2956821
|View full text |Cite
|
Sign up to set email alerts
|

Channel Characterization for Satellite Link and Terrestrial Link of Vehicular Communication in the mmWave Band

Abstract: In the vision of intelligent transportation, vehicles are expected to feature with advanced applications, such as automatic road enforcement, dynamic traffic light sequence, and autonomous driving. Therefore, real-time and fast dynamic information exchanges are required, and vehicle-to-everything (V2X) communications are highly demanded. In this work, the channel characteristics of vehicular communication are analyzed in the millimeter-wave (mmWave) band at 22.1-23.1 GHz. Specifically, two types of links (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…As mentioned in Section 4.2, our previous study [37] has shown that performance gains can be achieved by switching three beams appropriately at the V‐UE. Nevertheless, as in our other study [38], there is still a critical challenge that needs to be solved in the MNS. The study showed that in some cases, the received power of BS‐to‐V‐UE link is significantly degraded because of an unexpected blockage caused by the surroundings.…”
Section: Key Enabling Technologiesmentioning
confidence: 86%
See 4 more Smart Citations
“…As mentioned in Section 4.2, our previous study [37] has shown that performance gains can be achieved by switching three beams appropriately at the V‐UE. Nevertheless, as in our other study [38], there is still a critical challenge that needs to be solved in the MNS. The study showed that in some cases, the received power of BS‐to‐V‐UE link is significantly degraded because of an unexpected blockage caused by the surroundings.…”
Section: Key Enabling Technologiesmentioning
confidence: 86%
“…The received SNRs of the two traffic control schemes can be simply expressed as γ TS = max{ γ C , γ S } and γ JT = γ C + γ S , respectively, where γ C and γ S denote the SNRs received at the cellular and satellite receivers, respectively. In addition to the GEO satellite considered in the previous study [38], we further consider an LEO satellite with an altitude of 1500 km ( h 0 = 1500 km), which is one of the non‐GEO satellites given in [13]. Then, as in Refs [13,38], the distance d between the satellite and a V‐UE can be determined by elevation angle α and Earth radius R E , which can be expressed asd=RE20.166667emsin2α+h02+2h0RERE0.166667emsin0.166667emα,where R E = 6371 km, and considering that the elevation angles of GEO satellites in Korea are around 45°, the same elevation angle for both GEO and LEO satellites, α = 45°, is assumed for the sake of simplifying the analysis.…”
Section: Key Enabling Technologiesmentioning
confidence: 99%
See 3 more Smart Citations